A study to identify the stock market participation and investment portfolio preferences of legislators. (2017) - Cheng, Ching-Hsue; Chen, You-Shyang; Chen, Da-Ren; Lin, Shih-Han
This study identified the determinants of legislator participation in the stock market and investment portfolio preference. All of the data used for this study were hand collected during 2010-2013 from the property declarations provided by legislators to the Sunshine Acts website of the Control Yuan, Republic of China (Taiwan). Statistical analysis shows that all of the legislators studied have a high education level and relatively uniform above-average assets. The study findings indicate that the stock market participation of legislators is strongly associated with political orientation, higher education level, and higher wealth than median citizens; the two most important factors influencing legislators to participate in the stock market are party and wealth. Furthermore, the wealth and education levels of Kuomintang party legislators are obviously higher than those of legislators of the other parties. The empirical results show that legislators prefer stocks in the electronic and others categories more than those in other categories. This information provides evidence that legislators use their political power in ruling legislative processes to impact the stock price of listed-stock firms, thereby benefitting their investments. In conclusion, this work is focussed on helping voters to understand the implied information behind the ruling effect of legislators.